2002
DOI: 10.1080/10408360290795510
|View full text |Cite
|
Sign up to set email alerts
|

Polyadenylate Polymerase (PAP) and 3' End pre-mRNA Processing: Function, Assays, and Association with Disease

Abstract: Polyadenylate polymerase (PAP) is one of the enzymes involved in the formation of the polyadenylate tail of the 3' end of mRNA. Poly (A) tail formation is a significant component of 3' processing, a link in the chain of events, including transcription, splicing, and cleavage/polyadenylation of pre-mRNA. Transcription, capping, splicing, polyadenylation, and transport take place as coupled processes that can regulate one another. The poly(A) tail is found in almost all eukaryotic mRNA and is important in enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 176 publications
(221 reference statements)
2
18
0
2
Order By: Relevance
“…SUMO has a substantial impact on PAP function, and our data indicate that alterations in PAP sumoylation have the potential to profoundly affect gene expression. For example, misregulation of PAP activity has been associated with disease (for review, see Scorilas 2002). PAP activity is known to reflect the proliferative capacity of cells, as several neoplastic and leukaemic cells show increased PAP activity with or without increased PAP expression (Papamichail et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…SUMO has a substantial impact on PAP function, and our data indicate that alterations in PAP sumoylation have the potential to profoundly affect gene expression. For example, misregulation of PAP activity has been associated with disease (for review, see Scorilas 2002). PAP activity is known to reflect the proliferative capacity of cells, as several neoplastic and leukaemic cells show increased PAP activity with or without increased PAP expression (Papamichail et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The assembly of the cleavage/polyadenylation machinery requires specific signal sequences in the mRNA precursor as well as interactions of a large number of protein factors (reviewed by Mandel et al, 2008). It has been shown that the regulation of mRNA 3 0 end formation can have significant roles in cancer (Kleiman and Manley, 2001;Topalian et al, 2001;Scorilas, 2002;Rozenblatt-Rosen et al, 2009). Most importantly, alternative mRNA cleavage and polyadenylation changes the length of the 3 0 -untranslated region and regulates gene expression of different mRNAs in cancer cells (Mayr and Bartel 2009;Singh et al, 2009) and during cell differentiation (Sandberg et al, 2008;Zlotorynski and Agami, 2008;Ji et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The cloned sequences of bovine and human eNOS mRNAs were reported to have 3Ј poly(A) tails Ϸ12 to 20 nucleotides in length. 21,22 Although these studies did not specifically examine poly(A) tail length, the eNOS sequences were derived from RNA libraries of cultured cells not exposed to shear, suggesting that eNOS mRNA has a short 3Ј poly(A) tail under baseline conditions.…”
mentioning
confidence: 99%